Macro-event recognition in healthy ageing, Alzheimer’s disease, and mild cognitive impairment - Kokje, Eesha; Gerwien, Johannes; Stutterheim, Christiane von (The journal of neuropsychology, 2021)
Event perception and cognition is integral to our everyday experience and functional ability. A commonly reported complaint in Alzheimer’s disease (AD) is the inability to follow narratives - be it textual, conversational, video, or pictures. This phenomenon has received little systematic research so far. In the current study, we developed a novel paradigm to examine macro-event recognition in individuals with AD in the early stage and its preceding stage of mild cognitive impairment (MCI) in comparison with cognitively healthy older adults, using pictures depicting events. In Experiment 1, we examined participants’ ability to integrate pictorially depicted sub-events into macro-events. The pictures were presented in a scrambled order, and participants were expected to arrange them in the temporally and causally appropriate sequence, as dictated by the macro-event schema. Additionally, we investigated the effect of cueing the appropriate event schema by providing a word cue (verb). In Experiment 2, macro-event recognition was examined again using a cognitively less taxing paradigm, where pictures depicting sub-events were presented in correct order, but staggered, and recognition speed was measured. We observed significant deficits in the AD and MCI groups’ performance compared with the cognitively healthy older adults, across both experiments, suggesting event perception and cognition is impaired early in the course of AD. There was no effect of cueing on the performance of any of the groups. The theoretical and clinical implications of these findings are discussed.